2013
DOI: 10.1002/rhc3.20
|View full text |Cite
|
Sign up to set email alerts
|

Only Connect!” Social Capital, Resilience, and Recovery

Abstract: 's Building Resilience combines theoretical insights on the role of social capital in community life and extensive empirical research on its impact on recovery following four disasters. In her review of this major contribution, Kathleen Tierney discusses the conceptualization and measurement of disaster recovery and resilience and the relevance of social capital in its multiple forms. She then highlights potential contributions of supra-local entities to improving disaster outcomes that Aldrich seems reluctant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…For household characteristics, income and loss both have a significant negative relationship to household relocation willingness, consistent with Bateman and Edwards' (2002) study, but inconsistent with other studies (Whitehead et al 2000;Huang et al 2012;Stein et al 2013;Lazo et al 2015). Social support has a positive significant relationship to household relocation willingness, consistent with Tierney's (2013) study, but inconsistent with Riad et al's (1999) study. In our study, distance to hazard, household size, children, older people, Lim et al 2016).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…For household characteristics, income and loss both have a significant negative relationship to household relocation willingness, consistent with Bateman and Edwards' (2002) study, but inconsistent with other studies (Whitehead et al 2000;Huang et al 2012;Stein et al 2013;Lazo et al 2015). Social support has a positive significant relationship to household relocation willingness, consistent with Tierney's (2013) study, but inconsistent with Riad et al's (1999) study. In our study, distance to hazard, household size, children, older people, Lim et al 2016).…”
Section: Discussionmentioning
confidence: 71%
“…Social networks not only relate to information about a disaster, but are also related to the sharing of resources and enhancing the ability of groups to resist external risk (Xu et al 2015a, b;Xu et al 2017). Tierney (2013) showed that people look to others for help with the evacuation decisionmaking process. Households with stronger perceived social support were far more likely to evacuate than those with weaker perceived social support, but network size did not predict evacuation (Riad et al 1999).…”
Section: Household Characteristics and Relocation/ Evacuation Willingmentioning
confidence: 99%
“…If we hope to advance ongoing debates about whether long‐term mobility mitigates risks or destroys an established community, it is important to determine what factors influence residents’ plans to leave. The understanding of longer‐term mobility plans is particularly important as disaster‐affected residents try to re‐establish a sense of normalcy, often called “ontological security” (Hawkins & Maurer, ) or a “new normal” (Gotham, Blum, & Campanella, ; Tierney, ), a state that Turner () calls “a stage of culture readjustment… in which prolonged analyses are not undertaken, but only the minimal recognition of changed circumstances necessary to deal with the immediately pressing problems” inherent in the post‐disaster milieu (763; see also Dynes, ). Research on Florida's Hurricane Andrew indicates that residential relocation is associated with higher levels of medium‐term stress, isolation and social disruption (Riad & Norris, ), and increased economic hardship (Hori & Schafer, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Last, psychological and behavioral adjustments in individuals are needed in crisis management. Local leaders responding to crises must recognize that households suffer psychological, social, and economic harm, which must be addressed during the response to the crisis (Lindell et al, ; Olonilua & Ibitayo, ; Pearson & Clair, ; Tierney, ). Behavioral and psychological adjustments are needed so that households can contribute meaningfully to the building of more resilient units that can withstand future emergencies (Comfort, Siciliano, & Okada, ; Shimizu, ).…”
Section: Crisis Management Theory and Conceptsmentioning
confidence: 99%